A New Location System for an Underground Mining Environment Using Visible Light Communications - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2014)
In this paper we introduce a novel localization algorithm based on visible light communications (VLC) and the trilateration technique. The new algorithm can be used for tracking people or machinery in an underground mining environment. The proposed method utilizes the concept of reference points in order to reduce the location estimation error. The proposed algorithm outperforms the LANDMARC (location identification based on dynamic active radio frequency identification (RFID) calibration) algorithm, which uses RFID tags to determine the location of an object, in terms of the location estimation error. © 2014 IEEE.